2003
DOI: 10.1242/jcs.00216
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a role for Munc18-2 and microtubules in mast cell granule exocytosis

Abstract: effector loop inhibited IgE-triggered exocytosis, while increased expression of Munc18-3 showed no effect. Munc18-2 localisation on granules is polarised; however, upon stimulation Munc18-2 redistributed into forming lamellipodia and persisted on granules that were aligned along microtubules, but was excluded from F-actin ruffles. Disruption of the microtubule network with nocodazole provoked Munc18-2 redistribution and affected mediator release. These findings suggest a role for Munc18-2 and the microtubule n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
110
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 66 publications
13
110
1
Order By: Relevance
“…This finding is in accordance with previously published data demonstrating microtubule-dependent movement of secretory vesicles during exocytotic response (16,17,20) and studies documenting a dramatic decrease in degranulation, but not in Ca 2+ response in nocodazole treated cells (49). Our observation that STIM1 puncta are associated with microtubules in protrusions (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is in accordance with previously published data demonstrating microtubule-dependent movement of secretory vesicles during exocytotic response (16,17,20) and studies documenting a dramatic decrease in degranulation, but not in Ca 2+ response in nocodazole treated cells (49). Our observation that STIM1 puncta are associated with microtubules in protrusions (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Accumulating recent data point to an important role of microtubules in these processes (38). Previous studies focused primarily on the role of microtubules in granular transport (13,16,17,20) or on the initial stages of SOCE signaling pathway (13,15,39). In this study, we show that microtubule network rearrangement in activated BMMCs and formation of microtubule protrusions is dependent on the activity of Ca 2+ sensor STIM1.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Accumulating data point to the importance of microtubules in this process (3,4,7,34). We showed previously that the stimulation of mast cells or basophils through FcεRI aggregation or by pervanadate exposure triggers the generation of complexes containing g-tubulin, tyrosine-phosphorylated proteins, and tyrosine kinases (5,35) and the reorganization of microtubules (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules, built up from ab-tubulin heterodimers, are important for mast cell degranulation, because the movement of secretory granules depends on intact microtubules (2,3), and compounds inhibiting tubulin polymerization suppress degranulation (4). It was reported that FcεRI aggregation leads to reorganization of microtubules (3,5) and that the influx of Ca 2+ plays a decisive role in microtubule remodeling (6,7).…”
mentioning
confidence: 99%